O przypisach w Ewangeliach z Biblii brzeskiej z internetowej edycji Szesnastowieczne przekłady Ewangelii - Kępińska, Alina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article attempts to analyse different types of original glosses and editorial footnotes in the Gospels of the Brest Bible, one of ten Polish translations of the Bible, included in the electronic publication of Szesnastowieczne przekłady Ewangelii (Eng. Sixteenth-Century Translations of the Gospels). Among the original glosses one can distinguish: a) concordant glosses, referring to the parallel fragments of the Bible, b) philologicalexegetic glosses signed with capital letters of the alphabet. The greater part of original glosses of this kind includes annotations that are didactic and doctrinal comments. The marginal glosses signed with capital letters are also short lexical glosses which contain synonyms or definitions of words, including those referring to biblical reality. The contemporary editorial footnotes are different types of footnotes, including: substantive, graphic, inflectional, derivational and phonetic. Short descriptions of each type of footnotes focus on selected and more detailed aspects, e.g. the study of derivational footnotes provides information on the techniques of creating possessive adjectives often used in the text. The article draws upon new research techniques – a computer program Ewangelie (Gospels) and Internet search engine of annotations (https://ewangelie. uw.edu.pl/przypisy) by Michał Rudolf.